2016
DOI: 10.1038/srep25563
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of size modulation and conventional standard automated perimetry with the 24-2 test protocol in glaucoma patients

Abstract: This prospective randomized study compared test results of size modulation standard automated perimetry (SM-SAP) performed with the Octopus 600 and conventional SAP (C-SAP) performed with the Humphrey Field Analyzer (HFA) in glaucoma patients. Eighty-eight eyes of 88 glaucoma patients underwent SM-SAP and C-SAP tests with the Octopus 600 24-2 Dynamic and HFA 24-2 SITA-Standard, respectively. Fovea threshold, mean defect, and square loss variance of SM-SAP were significantly correlated with the corresponding C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In early damage, several groups have reported that size modulation perimetry shows promise, because it may have a better signal-to-noise ratio than conventional perimetry (where size remains constant but contrast is modulated), in particular for detection of defects. 47 49 This finding is particularly true if stimuli are configured to remain smaller than Ricco's area of complete spatial summation, which expands in glaucoma. 49 However, RGC receptive fields exhibit a center-surround organization.…”
Section: Discussionmentioning
confidence: 99%
“…In early damage, several groups have reported that size modulation perimetry shows promise, because it may have a better signal-to-noise ratio than conventional perimetry (where size remains constant but contrast is modulated), in particular for detection of defects. 47 49 This finding is particularly true if stimuli are configured to remain smaller than Ricco's area of complete spatial summation, which expands in glaucoma. 49 However, RGC receptive fields exhibit a center-surround organization.…”
Section: Discussionmentioning
confidence: 99%
“…The size modulation formula has been described previously. 2 , 19 The perimeter uses the size modulation technique for SAP; thus, maintaining the spatial summation of the stimuli within a dynamic range of 0 to 35 dB. The background luminance and maximum stimulus intensity of the Octopus 600 perimeter are 31.4 and 417 apostilb, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although the threshold strategy helps measure retinal sensitivity at each test point more accurately, it also requires greater time for measurement — 5 to 10 minutes with the Swedish Interactive Threshold Algorithm (SITA)-Standard and 3 to 5 minutes with the SITA-Fast, using the Humphrey Field Analyzer (HFA), 1 4 to 7 minutes with the Dynamic strategy, 2,3 and 2 to 4 minutes with the Tendency Oriented Perimetry strategy 4,5 using the Octopus perimeter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation